2018
DOI: 10.1136/tobaccocontrol-2018-054325
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial function is impaired by aerosol from a single IQOS HeatStick to the same extent as by cigarette smoke

Abstract: Background Heated tobacco products (also called “heat-not-burn” products) heat tobacco at temperatures below that of combustion, causing nicotine and other compounds to aerosolize. One such product, IQOS from Philip Morris International, is being marketed internationally with claims of harm reduction. We sought to determine whether exposure to IQOS aerosol impairs arterial flow-mediated dilation (FMD), a measure of vascular endothelial function that is impaired by tobacco smoke. Methods We exposed anesthetiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 49 publications
3
71
0
2
Order By: Relevance
“…Based on evidence from studies not sponsored by the tobacco company, in general, the results have shown that HTP use releases lower levels of most toxic chemicals and harmful substances compared to conventional cigarettes. However, toxic compounds are not completely removed IJOMEH 2019;32(5) [71] to determine the potential impact of exposure to the IQOS aerosol on arterial flow-mediated dilation 8 male rats; anaesthetized rats were exposed to the IQOS aerosol from single HeatSticks, mainstream smoke from single cigarettes or clean air for a series of consecutive 30-s cycles over 1.5-5 min; each cycle -15 or 5 s of exposure, followed by removal from the nose cone; measurement: pre-exposure and post-exposure flow-mediated dilation, and post-exposure serum nicotine and cotinine -acute exposures to the IQOS aerosol impair the flow-mediated dilation in rats the mainstream IQOS aerosol from a single HeatStick can rapidly and substantially impair the endothelial function in rats, comparably to cigarette smoke the post-exposure serum nicotine levels were 4.5-fold higher in the rats exposed to IQOS than in those exposed to cigarettes Leigh et al, USA (2018) [72] to examine the potential cytotoxic effects of inhaling emissions from an HTP, in comparison with the electronic and combustible cigarettes. human bronchial epithelial cells exposed directly to 1) 55 puffs from an e-cigarette, 2) 12 puffs from an HTP, and…”
Section: Evidence From the Experimental Animal And Cellular Studiesmentioning
confidence: 99%
“…Based on evidence from studies not sponsored by the tobacco company, in general, the results have shown that HTP use releases lower levels of most toxic chemicals and harmful substances compared to conventional cigarettes. However, toxic compounds are not completely removed IJOMEH 2019;32(5) [71] to determine the potential impact of exposure to the IQOS aerosol on arterial flow-mediated dilation 8 male rats; anaesthetized rats were exposed to the IQOS aerosol from single HeatSticks, mainstream smoke from single cigarettes or clean air for a series of consecutive 30-s cycles over 1.5-5 min; each cycle -15 or 5 s of exposure, followed by removal from the nose cone; measurement: pre-exposure and post-exposure flow-mediated dilation, and post-exposure serum nicotine and cotinine -acute exposures to the IQOS aerosol impair the flow-mediated dilation in rats the mainstream IQOS aerosol from a single HeatStick can rapidly and substantially impair the endothelial function in rats, comparably to cigarette smoke the post-exposure serum nicotine levels were 4.5-fold higher in the rats exposed to IQOS than in those exposed to cigarettes Leigh et al, USA (2018) [72] to examine the potential cytotoxic effects of inhaling emissions from an HTP, in comparison with the electronic and combustible cigarettes. human bronchial epithelial cells exposed directly to 1) 55 puffs from an e-cigarette, 2) 12 puffs from an HTP, and…”
Section: Evidence From the Experimental Animal And Cellular Studiesmentioning
confidence: 99%
“…3,28,29 It is likely, however, that the difference in nicotine absorption from JUUL and conventional e-cig aerosol does not directly dictate the magnitude of the vascular response, which we have already observed to be saturating in this model even by very brief (2 seconds) mainstream exposures to cigarette smoke and IQOS aerosol. 20 While we have reported a positive correlation between the concentration of nicotine in heavily diluted tobacco sidestream smoke and the extent to which FMD is impaired in rats exposed to it, 30 the fact that FMD is still impaired in humans inhaling nicotine-free e-cig aerosol 22 and in rats inhaling marijuana sidestream smoke 19 indicates that the nicotine is not the main driver of this effect.…”
Section: Serum Nicotine Was Highest In Rats That Were Exposed To Juulmentioning
confidence: 83%
“…12,15 Using this technique, we showed that FMD is also impaired in rats by brief exposures to mainstream and sidestream smoke or mainstream aerosols from cigarettes, little cigars, combustible marijuana, and IQOS "heat-not-burn" tobacco products. [17][18][19][20] Acute use of e-cigs 8/30/19 4 with or without nicotine in humans impairs several measures of endothelial function including FMD 21,22 and we have reported that nitric oxide production from cultured endothelial cells is impaired when the cells are incubated in serum from chronic e-cig use. 23 Here we report that acute mainstream exposure to aerosol from JUUL or from previous generation e-cigs using freebase nicotine impairs vascular function comparably to combusted cigarette smoke and delivers considerably more nicotine to the blood on a per puff basis.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Second, PMI has ridiculously called its new product IQOS (for “I quit ordinary smoking”). Multiple independent scientific assessments suggest that IQOS can be very harmful and the device is so new that its harm has not been fully uncovered/experienced. Yet PMI is trying to curb regulatory defences.…”
Section: A Few News Stories In the Order Retrieved From Google News Smentioning
confidence: 99%